2019
DOI: 10.2147/opth.s176120
|View full text |Cite
|
Sign up to set email alerts
|

<p>Idiopathic epiretinal membrane surgery: safety, efficacy and patient related outcomes</p>

Abstract: This review aims to give to the reader an overview selectively oriented on safety and efficacy of surgery, providing concise and direct answers about crucial questions of trainees and experts. Surgery for idiopathic epiretinal membrane (ERM) is a safe and effective procedure that can achieve long-term stable postoperative visual and anatomical improvement, with an overall low recurrence and complication rate. Young patients, with a short onset of symptoms and with better initial visual acuity achieve higher le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 92 publications
1
31
1
2
Order By: Relevance
“…Although metamorphopsia and visual impairment could be improved in approximately 70–90% of postoperative ERM cases ( De Bustros et al, 1988 ; Iuliano et al, 2019 ), these symptoms persist in some ERM patients. Predicting postoperative outcomes and weighing the risks and benefits of surgery are important because there are currently no standardized surgical indicators for ERM ( Diaz-Valverde & Wu, 2018 ; Nakashizuka et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although metamorphopsia and visual impairment could be improved in approximately 70–90% of postoperative ERM cases ( De Bustros et al, 1988 ; Iuliano et al, 2019 ), these symptoms persist in some ERM patients. Predicting postoperative outcomes and weighing the risks and benefits of surgery are important because there are currently no standardized surgical indicators for ERM ( Diaz-Valverde & Wu, 2018 ; Nakashizuka et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported OCT measurements which correlate to visual prognosis, with attempts at incorporating such biomarkers into newer ERM classification systems. Features on OCT predicting a better prognosis include: absence of EIFL, 90‐92 inner retinal irregularity, CMO 93 or acquired vitelliform lesions 89 ; preserved integrity of the EZ 83,93,94 and COST 94 ; and thinner CFT and preoperative ganglion cell layer‐inner plexiform layer (GCL‐IPL) 95,96 …”
Section: Investigationsmentioning
confidence: 99%
“…In addition, OCT imaging has provided insights into post‐surgical retinal damage which can occur, particularly with ERM/ILM double peeling. However, there is little evidence that postoperative changes on SD‐OCT are linked to poorer VA or even changes on microperimetry 95 …”
Section: Managementmentioning
confidence: 99%
“…However, increased comorbidities were the primary consideration in most areas, especially the Eastern region. Surgery for ERMs is important to improve patients' longterm visual condition (13). The peeling of ILM is applied as an accessory procedure to improve the curative effect, (14) and results in a lower recurrence rate (15).…”
Section: The Choice Of Conservative Treatment Versus Erm Surgerymentioning
confidence: 99%